2017
DOI: 10.1364/oe.25.023267
|View full text |Cite
|
Sign up to set email alerts
|

71-Mbit/s ultraviolet-B LED communication link based on 8-QAM-OFDM modulation

Abstract: A demonstration of ultraviolet-B (UVB) communication link is implemented utilizing quadrature amplitude modulation (QAM) orthogonal frequency-division multiplexing (OFDM). The demonstration is based on a 294-nm UVB-light-emitting-diode (UVB-LED) with a full-width at half-maximum (FWHM) of 9 nm and light output power of 190 μW, at 7 V, with a special silica gel lens on top of it. A -3-dB bandwidth of 29 MHz was measured and a high-speed near-solar-blind communication link with a data rate of 71 Mbit/s was achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…It is noted that attenuations and multiple paths, brought about by absorption and scattering, can be diminished by using extremely sensitive detectors, such as PMTs and intersymbol-interference mitigation modulation schemes, such as OFDM. 141) In the absence of compact and energy efficient UV devices, including UV transmitter and receiver, theoretical modeling was the focus of majority of the early work. Experimental studies on UV optical communications dated back to as early as 1964, 142) in which discussions on system components including sources, filters, and receivers were provided.…”
Section: Los and Nlos Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that attenuations and multiple paths, brought about by absorption and scattering, can be diminished by using extremely sensitive detectors, such as PMTs and intersymbol-interference mitigation modulation schemes, such as OFDM. 141) In the absence of compact and energy efficient UV devices, including UV transmitter and receiver, theoretical modeling was the focus of majority of the early work. Experimental studies on UV optical communications dated back to as early as 1964, 142) in which discussions on system components including sources, filters, and receivers were provided.…”
Section: Los and Nlos Communicationsmentioning
confidence: 99%
“…In 2012, an experimental NLOS test-bed utilizing a 265-nm UVC LED and diversity reception technology integrated with equalgain-combining (EGC) scheme and modulated by OOK demonstrated a data rate of 2.4 kbps over 100 m. 148) Very recently, a diffuse-LOS communication link with high datarate of 71 Mbps was implemented by using a 294 nm UVB LED and an APD. 141) In the experiment, OFDM modulation was adopted to mitigate intersymbol-interference (ISI) for improving link performance. Table IV provides a summary of data rates achieved in those studies.…”
Section: Los and Nlos Communicationsmentioning
confidence: 99%
“…The aforementioned advantages, as well as the recent development in solid-state UVC light-emitting diodes (LEDs) and high-speed low-cost detectors [1], make UVC OWC a promising communication technology, but maintaining high speeds over practical distances has been a challenge. In [2], a 71megabit-per-second diffuse-LOS link was demonstrated based on a 294-nm LED operating in the ultraviolet-B (UVB) regime over a short distance of only 8 cm. In 2019, a LOS 1.5-m link was tested in an outdoor environment using a 280-nm LED with a data rate of 1.18 gigabit-per-second (Gbps) [3], and a similar system was used in [4] to establish a 2-Gbps indoor link over 1.5 m. Using a micro-LED emitting light at a wavelength of 262 nm, He et al demonstrated a 1.1-Gbps LOS link, but the distance was limited to 30 cm due to the limited LED power [5].…”
Section: Introductionmentioning
confidence: 99%
“…While the radio frequency (RF) spectrum has reached its limits by offering frequencies up to 300 GHz, optical wireless technologies offer a free and unlicensed spectrum that is 1000 times wider than that of the RF spectrum. Therefore, optical wireless communication and especially visible light communication (VLC) has seen a major growth and lots of potential in the past decade [1]- [4].…”
Section: Introductionmentioning
confidence: 99%